Emotion and Its Critical Scales - Sayeed, Sayed Ahmad (Journal of Social Sciences - Kabul University, 2022)
This article explores the concept of emotion and its critical scales by examining its definition, classifications, principles, theories, and underlying requirements. It also delves into the dynamics of strong and diverse emotions in literature, emphasizing the role of imagination, thought, and verbal context in conveying intended meanings. The failure to observe the contextual integrity of an ode often signifies the intensity of emotional shifts, leading to critical evaluation. A strong emotional presence enhances poetry, making it engaging, lively, and captivating. Conversely, the absence of emotional depth weakens the poetic experience. This can be understood through the melodies of an ode, its rhetorical richness, and its stylistic techniques. Considering stability, continuity, and literary criticism, emotion is analyzed from multiple perspectives—its meaning, structure, stylistic expression, and imaginative depth. Arab literary critics recognized the essence of emotion, though it was not always systematically categorized in idiomatic or methodological terms. Some poetry, despite its precision and authority, lacked sweetness and appeal, while other compositions, though beautiful, did not necessarily exhibit subtlety and expressiveness. The most effective poetry seamlessly integrates structure and meaning, resonates with the heart, and leaves a lasting impression on the soul.